2023
DOI: 10.1111/jrh.12751
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccination willingness and uptake among rural Black/African American, Latino, and White adults

Abstract: PurposeThe purpose of this study was to assess differences in COVID‐19 vaccine willingness and uptake between rural and nonrural adults, and within rural racial‐ethnic groups.MethodsWe utilized data from the COVID‐19's Unequal Racial Burden online survey, which included 1,500 Black/African American, Latino, and White rural adults (n = 500 each). Baseline (12/2020‐2/2021) and 6‐month follow‐up (8/2021‐9/2021) surveys were administered. A cohort of nonrural Black/African American, Latino, and White adults (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…These results mirror previously published findings in our rural adult cohort ( Strassle et al, 2023 ). Similarly to low-income White adults, rural White adults were less willing to be vaccinated and less likely to be vaccinated compared to non-rural White adults.…”
Section: Discussionsupporting
confidence: 93%
“…These results mirror previously published findings in our rural adult cohort ( Strassle et al, 2023 ). Similarly to low-income White adults, rural White adults were less willing to be vaccinated and less likely to be vaccinated compared to non-rural White adults.…”
Section: Discussionsupporting
confidence: 93%
“…Information on the development of the CURB survey for the main sample 29,30 and the rural sample 31 has been detailed elsewhere. CURB participants were recruited from the YouGov proprietary, opt-in survey panel comprised of over 1.8 million US residents recruited through a variety of methods (eg, telephone-to-Web recruitment, mail-to-Web recruitment) to help ensure diversity.…”
Section: Methodsmentioning
confidence: 99%
“…However, the link between these aggregate associations and individual factors remains underexplored. In one of the only extant studies on individual-level rural vaccine behavior, to our knowledge, Strassle et al (2023) found that over 25 % of rural adults who were initially extremely against vaccination ultimately received the vaccine, and that there was no significant variation in actual vaccine behavior across racial groups. Our study extends the work of Strassle et al (2023) by using a different, yet comparable dataset, focusing on factors beyond race and ethnicity, and examining vaccine behavior as it relates to dependent children.…”
Section: Introductionmentioning
confidence: 88%